REVIEW OF FISH FEED DISTRIBUTION STRATEGY AT PT INGIN SEJAHTERA MANDIRI IN PASAMAN REGENCY - Firdaus Husein; Dwi Yuzaria; Fachrul Roji (Universitas Mataram, 2026)
Fish feed distribution plays a crucial role in supporting the efficiency and sustainability of aquaculture activities. PT Ingin Sejahtera Mandiri, as one of the fish feed distributors in Pasaman Regency, faces several challenges related to distribution channel effectiveness, delivery timeliness, and price accessibility for fish farmers. This study aims to review and analyze the fish feed distribution strategies implemented by PT Ingin Sejahtera Mandiri and to identify factors influencing distribution performance. The research employed a descriptive qualitative approach, with data collected through interviews, field observations, and document analysis. The data were analyzed to evaluate distribution patterns, logistics systems, and the company’s relationships with partners and customers. The results indicate that the distribution strategy is mainly based on direct and indirect distribution through agents, with major constraints including limited transportation facilities, long distribution distances, and fluctuating feed demand. Nevertheless, the company has significant potential to improve distribution effectiveness by strengthening supply chain management, adopting information technology, and optimizing local distribution networks. This study is expected to provide practical insights for the company and contribute to the development of more efficient and sustainable fish feed distribution strategies in Pasaman Regency.